2015
DOI: 10.17269/cjph.106.4794
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sedentary behaviour of toddlers and preschoolers in child care centres in Alberta, Canada

Abstract: This is the first Canadian study to report on the duration of physical activity and duration and bouts of sedentary behaviour among both toddlers and preschoolers attending child care centres. These findings suggest child care interventions are needed to increase MVPA and decrease total sedentary behaviour while continuing to promote short sedentary bouts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 29 publications
5
29
1
Order By: Relevance
“…Specifically, children in our study spent 63% of the time in childcare in sedentary activity and only 2% in MVPA, which is almost identical to the results of a study of preschoolers in Alberta, Canada, which found that participants spent 62% of their time in sedentary activity and 4% in MVPA (Kuzik et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Specifically, children in our study spent 63% of the time in childcare in sedentary activity and only 2% in MVPA, which is almost identical to the results of a study of preschoolers in Alberta, Canada, which found that participants spent 62% of their time in sedentary activity and 4% in MVPA (Kuzik et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…However, many preschoolers consume low amounts of vegetables and fruit, and excessive amounts of saturated fat and added sugars while in childcare centers (Ball et al, 2008;Copeland et al, 2013;Erinosho et al, 2013;Gubbels et al, 2014). Furthermore, despite opportunities for children to be active inside and outside, studies have consistently shown that sedentary time within childcare centers is typically high, while physical activity levels are typically very low, accumulating less than 20 minutes per day of moderate-to-vigorous physical activity (MVPA) during an 8-hour day (Kuzik et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with those reported by Kuzik and colleagues [24], who objectively measured bouts of sedentary behavior in a sample of toddlers and preschoolers attending center-based child care in Alberta, Canada. In that study, sedentary behaviors over the child care day were accumulated primarily in short bouts, lasting 1 to 4 min, with almost no engagement in extended bouts lasting 15 min or longer.…”
Section: Discussionsupporting
confidence: 92%
“…This study described the frequency and duration of sedentary bouts in children attending FCCHs in the northwestern region of the United States. Consistent with the results of studies conducted in center-based child care settings [24], children attending FCCHs accumulated very little sedentary time in long or extended bouts lasting more than 10 min. Children in the current study mostly accumulated sedentary time in short bouts (1-4 min).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation